Keyphrase Generation for Scientific Articles Using GANs (Student Abstract) - Swaminathan, Avinash; Gupta, Raj Kuwar; Zhang, Haimin; Mahata, Debanjan; Gosangi, Rakesh; Shah, Rajiv Ratn (Proceedings of the AAAI Conference on Artificial Intelligence, 2020)
In this paper, we present a keyphrase generation approach using conditional Generative Adversarial Networks (GAN). In our GAN model, the generator outputs a sequence of keyphrases based on the title and abstract of a scientific article. The discriminator learns to distinguish between machine-generated and human-curated keyphrases. We evaluate this approach on standard benchmark datasets. Our model achieves state-of-the-art performance in generation of abstractive keyphrases and is also comparable to the best performing extractive techniques. We also demonstrate that our method generates more diverse keyphrases and make our implementation publicly available1.